Assessing the Economic Impact of the ECOWAS CET and Economic Partnership Agreement on Ghana - World Bank Group (World Bank, Washington, DC, 2015)
Ghana is currently facing two major trade policy adjustments - the economic community of West African states (ECOWAS) common external tariff (CET) is a significant milestone within the long history of regional integration in West Africa. In addition to the CET, Ghana faces the economic partnership agreement (EPA) with the European Union, which has been designed to build on the CET in West Africa. This study aims to enhance the debate by presenting an intuitive and data-driven technical perspective on the likely effects of the CET and the EPA. The study seeks to improve the information available to policy makers in Ghana. This is highly relevant, as the CET currently awaits parliamentary approval and the EPA will soon also require ratification. The study also aims to expand the information with which policy makers can develop accompanying policies to support and derive maximum benefit from the CET and EPA trade reforms. The first stage of the study employs the trade reform impact simulation tool (TRIST), which was developed by the World Bank. The study uses the finalized CET and EPA tariff schedules at the most detailed (10-digit) tariff line level, and 2013 customs excise and preventive service (CEPS) data on imports, exemption rates, tariff revenue, value-added tax (VAT), and national health insurance levy (NHIL) revenue, excise duty, and the over-age penalty for vehicles. The report presents the results for six scenarios: (1) the effect of the CET only, which is to be implemented before the end of 2015; the effect of each stage of the EPA implemented on top of the CET, (2) CET + EPA2020, (3) CET + EPA2025, (4) CET + EPA2030, (5) CET + EPA2035, and (6) the net effect of the EPA, where the EPA is implemented from a baseline where the CET is already in place (EPA2035 from CET). The study is structured as follows: section one gives introduction. Section two summarizes the market access content of the CET and EPA. Section three analyzes the effects of each reform on revenues and imports, section four looks at the effects on consumers, and section five examines the effects on firms’ competitiveness and jobs. Section six looks at potential accompanying measures and section seven concludes.